Physicochemical and phytochemical standardization, and antibacterial evaluation of Cassia alata leaves from different locations in Indonesia - Marissa Angelina; Ainul Mardhiyah; Rizna Triana Dewi; Sofa Fajriah; Nusaibah Muthiah; Yasmin Ekapratiwi; Indah D. Dewijanti; Sukirno; Jamilah; Sri Hartati (Pensoft Publishers, 2021)
Physicochemical analysis for simplicia and extract, respectively: water content 2.12-4% for simplicia; drying losses 3.93-5.47% and 8.51-19.76%; total ash 5.14-9.41% and 6.22-17.07%; total ash acid-insoluble content 0.29-5.41% and 0.52-3.82%; total ash water-soluble content 1.26-7.14% and 1.43-8.54%; water-soluble content 19.60-39.43% and 58.45-77.51%; ethanol-soluble content 13.99-33.76% and 59.79-75.39%. The phytochemical analysis showed that the extracts contain alkaloids, flavonoids, saponins, tannins, and terpenoids. Total flavonoids and total phenolics content were 9.86-15.74% QE/g and 6.67-7.65% GAE/g, respectively. Based on LC-MS results, the extract contained emodin, kaempferol, kaempferol-3,7-diglucoside, and kaempferol-3-O-β-D-glucopyranoside. The extracts possessed antibacterial activity against bacteria tested.